Living Curriculum As An Ethnopedagogical Approach To Religius Moderation In Pancasila Village - Simamora, Izzatul Salsa Bila; Maghfiroh, Novita Lailatul; Hijrianti, Nur; Arifah, Laily Nur (Proceeding of International Conference on Islamic Education (ICIED); Vol 10 No 1 (2025): Proceeding of International Conference on Islamic Education (ICIED), 2025)
This study aims to analyze the application of a sustainable living curriculum in the Pancasila village in strengthening religious moderation with an ethnopedagogical approach. Living curriculum is understood as a practice of tolerance and unity education that is not only obtained through formal education, but can be channeled through daily life. The research method used is qualitative-descriptive with an ethnopedagogical study approach through interviews, observations, participatory, and field documentation. This research involved several resource persons including: Chairman of the Rukun Warga (RW), religious leaders, and the community. The results of this study prove that the implementation of the living curriculum in the Pancasila village is carried out in joint activities such as holiday celebrations, community deliberations, tumpengan, arts, ecology, and mutual cooperation. All of these activities are carried out by all residents without any differences. The value of religious moderation is inherited through parental education, the role of religious leaders, and the participation of the younger generation in socio-religious activities. This study confirms that the living curriculum ethnopedagogical approach is an effective, contextual, and sustainable character education model in the application of religious moderation in Indonesia's multicultural society.